Evaluación de un sistema de asociación maíz (zea mays l.) con frejol Caupi (vigna .unguiculata l. Wa/p) en la estación experimental El Porvenir Juan Guerra - San Martín - Panduro Saavedra, Aurelio (2001)
Presently work the field phase was developed in the environment of the EE. "El Porvenir" in Juan Guerra Distríct, County, Department and Regíon of San Martin, among the months of January-June of the 2000 geographically characterízed by the cordenadas 76°5 'longitud west, 6°35 'latitud south and an altitude of 356 m.s.n.m. With the objective of evaluating the system of cornleguminous association and the productivity for unit of equivalent of earth (U:E:T). The used experimental design was the design of B!Ocks Completely Randomizado (BCR) with 4 repetitions and six treatments including the monocultivos of corn and bean. The treatments in study are: T1 (com monocultivo sowed 0.80m x 0.40m), T2 (bean monocultivo sowed 0.80m x0.30m), T3 (an array of corn inserted with a bean array sowed to 1.0m x 0,50m and the bean to 1.0m x 0.30m), T4 (an array of com inserted with two bean arrays sowed 1.0m x 0.50m and the bean to 0.50m x 0.30m), T5 (two arrays of corn inserted with two bean arrays sowed 1.0m x 1.0m and the bean to 0.50m x 0.3om), T6 (corn more bean inserted in the same line sowed 1,0m x 0,50m). Developed the rehearsal demonstrates us that the siembra associated of the treatments T5 and T4, híghlighted for its biggest ability in the grain yield the T5 it shows this way a yield of 4690 kg/ha, T4 4090 kg/ha, followed by the treatment witness corn with 4480 kgha. The association com-caupi sample a better equivalent index of earth (IET) in comparison with their respective monocultivos, as consequence of a better use in the use of the floor. As for the economíc Benefit it shows us a net utility of 1456.44 new suns far there is for the T4 and according to the relationship Benefit-cost it was determined that the T4 shows bigger profltability, showing a gain of 73 cents for each invested sun not existing differences or economic losses.